Odpowiedzi

2010-03-19T17:16:42+01:00
15z + 3(1-2z)=9z
15z+3-6z=9z
15z-6z-9z=-3
0=-3

0,8 (2x-1) + 0,3 (4-5x) = 0
1,6x-0,8+1,2-1,5x=0
1,6x-1,5x=-1,2+0,8
0,1x=-0,4
x=-4
1 5 1
Najlepsza Odpowiedź!
2010-03-19T17:17:03+01:00
A)15z +3 - 6z=9z
9z + 3=9z
3=0
rown sprzeczne
b)1,6x - 0,8 +1,2 - 1,5x=0
0,1x+0,4=0
0,1x=-0,4
x=-4


(Ewela nie można dzielić przez 0 ;/)
1 5 1
2010-03-19T17:17:45+01:00
15z + 3(1-2z)=9z
15z+3-6z=9z
9z+3=9z
9z-9z=-3
0=-3/to dzielimy przez zero i mamy 0

b) 0,8 (2x-1) + 0,3 (4-5x) = 0

1,6x-0,8+1,2-1,5x=0
1,6x-1,5x=0,8-1,2
0,1(1/10)x=-0,4(4/10) /to mnożymy razy 10
x=-4
1 5 1